Building Democracy with Autocracy: A Case Study of the Personalisation of Political Parties in Indonesia - Rofiq, Rofiq; Zahra, Rijfa Tuhfah (JPP (Jurnal Politik Profetik), 2026)
Indonesia was the third-largest country at the beginning of the reform era, but its Democracy Index has declined significantly. Many factors, including leadership in political parties, have influenced this decline. This study aims to examine in greater depth the leadership of political parties in Indonesia, how party leadership works, and why the circulation of party leadership does not work. This study uses a qualitative case study approach. Five major parties, namely PDIP, PKB, Gerindra, NasDem and Demokrat, were selected as research subjects. This study found three problems in political parties. First, regulations are enacted to advance the elite’s desire to strengthen the party chairman’s position. Second, the dominance of a single leader prevents the circulation of internal party leadership. Party policies are centralised, weakening internal party democracy and closing off channels for ideas and thoughts to the decisions of a single individual. Third, the personalisation of party leaders through online media has led voters to increasingly rely on party leaders as guides in their decision-making, indicating a decline in the importance of party organisations. This study contributes to the field of political science and reinforces prior social and political science research, particularly on political parties in Indonesia.